Materializing performance and ritual: decoding the archaeology of movement in Tallensi shrines in northern Ghana - Insoll, Timothy (Material religion, 2009)
The static is often given prominence within much archaeological interpretation and conceptualization in relation to ritual and religion. This is potentially due to the fact that static material residues are being considered and, in turn, this static image is transferred onto the ritual practices, beliefs, and communities that generated the archaeological material. Instead some of the material encountered archaeologically might be structured by much more dynamic, fluid, and active ritual behaviors. Considering performance, movement, and bodily understandings in relation to space and material culture offers a potential mechanism to begin to explore this, and will be considered with reference to the Golib festival and the archaeology of Tallensi shrines in the Tongo Hills of the Upper East Region in Northern Ghana.